2016
DOI: 10.5539/ibr.v9n4p123
|View full text |Cite
|
Sign up to set email alerts
|

Sales Promotion Effectiveness: The Impact of Culture on Demographic Level

Abstract: Sales promotion is an essential tool which leads to real increase in sales and profit. According to previous studies, sales promotions are effective at a cross cultural level when they provide benefits that go hand in hand with those of the promoted product. However, there is no literature state about the different sales promotion consumer benefits influences on its effectiveness at the demographic level (urban verses rural). To address this concern, this paper seeks to explore the congruence framework by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Several findings concur monetary promotions are more effective for utilitarian products and nonmonetary ones for hedonic products (Chandon, Wansink, & Laurent, 2000;Santini, Sampaio, Perin, & Vieira, 2015). Huynh (2016) confirms the same finding and adds that urban consumers prefer nonmonetary promotions while rural people like the monetary ones. Palazn-Vial and Degado-Ballester (2005) discover non-monetary promotions have a stronger impact on long-term brand knowledge.…”
Section: Review Of Literaturesupporting
confidence: 69%
See 3 more Smart Citations
“…Several findings concur monetary promotions are more effective for utilitarian products and nonmonetary ones for hedonic products (Chandon, Wansink, & Laurent, 2000;Santini, Sampaio, Perin, & Vieira, 2015). Huynh (2016) confirms the same finding and adds that urban consumers prefer nonmonetary promotions while rural people like the monetary ones. Palazn-Vial and Degado-Ballester (2005) discover non-monetary promotions have a stronger impact on long-term brand knowledge.…”
Section: Review Of Literaturesupporting
confidence: 69%
“…Sales promotion groups also have significantly higher scores than advertising and are better than multiple tools for credibility and familiarity. The higher scores of sales promotion may result from the types of products or services which is the significant factor for using sales promotion as found in earlier studies (Chandon, Wansink, & Laurent, 2000;Huynh, 2016;Santini et al, 2015). In this study, the retail business depends mostly on sales promotion.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Marketing has gone beyond, the process of introducing a new product into the market, giving the product the right price, making them accessible or reachable to the target market. Attracting customers is so essential; to marketers, the cost of keeping old customers is far cheaper than gaining a new customer (Huynh, 2016). Mittal and Sethi (2011) explained that the cost and benefit analysis is critically done, it revealed that searching for a new customer is very expensive than keeping an existing customer.…”
Section: Introductionmentioning
confidence: 99%